Animal control officers to the rescue - Goldish, Meish (New York, N.Y. : Bearport Pub., 2013)
From rescuing six baby wild turkeys at the bottom of a storm drain to capturing a ten-foot-long (3-m) boa constrictor slithering through a Florida neighborhood, animal control officers are devoted to protecting animals and ensuring the safety of people.
On thin ice -- A daring rescue -- Different duties -- Job training -- Down the drain -- Night crawler -- A chimney hideaway -- Caging a coyote -- The long chase -- A deadly match -- Double trouble -- Why be an animal control officer?.
7 - 10 years
Keywords: Animal welfare -- United States; Animal welfare; United States; Juvenile works